2016
DOI: 10.1177/0954408914554021
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and tracking control of a nonlinear electrohydraulic valve-cylinder system

Abstract: It is well known that simple proportional, integral, and derivative control yields poor tracking performance due to the friction-and flow-related nonlinearities in electrohydraulic servo-systems. Nonlinear effects are more significant in proportional valve having deadband and non-matched ports with potential application in systems with complex ground friction in off-road vehicles or complex inertia loads in simulators meant for pilot training. A feedforwardbased controller has been designed here by performing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Within a range ± e 0 of the voltage variation, called the valve deadband, the leakage flow within the PV does not induce any perceptible piston motion. A previous study 29 on a similar system revealed the deadband as ±1.5 V. Beyond the deadband, the valve flow variation with the command voltage e was found as nonlinear, as highlighted in Figure 2(a). The figure additionally shows the associated pressure drop characteristics, where Δ P i ( i = 1 4 ) is the pressure drop across the proportional valve ports.…”
Section: Descriptions Of System and Controller Architecturementioning
confidence: 60%
See 2 more Smart Citations
“…Within a range ± e 0 of the voltage variation, called the valve deadband, the leakage flow within the PV does not induce any perceptible piston motion. A previous study 29 on a similar system revealed the deadband as ±1.5 V. Beyond the deadband, the valve flow variation with the command voltage e was found as nonlinear, as highlighted in Figure 2(a). The figure additionally shows the associated pressure drop characteristics, where Δ P i ( i = 1 4 ) is the pressure drop across the proportional valve ports.…”
Section: Descriptions Of System and Controller Architecturementioning
confidence: 60%
“…Figure 2 represents the system nonlinearities characterized earlier. 29 The flow and pressure drop of the proportional valve were determined experimentally, as shown in Figure 2(a) with Q r being the flow measured in the return line by a screw flow meter. Within a range ± e 0 of the voltage variation, called the valve deadband, the leakage flow within the PV does not induce any perceptible piston motion.…”
Section: Descriptions Of System and Controller Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…This can be calculated by measuring the pressure at both ends of the valve ports and the displacement of the valve spool. Das et al [13] and Borghi et al [14] used the polynomial equation with the flow rate as an independent variable to fit the pressure drop at both ends of the valve port for different valve openings. Åman et al [15] also used the pressure difference at both ends of the valve port to fit the flow rate through the valve port on the basis of considering the influence of the flow patterns.…”
Section: Indirect State Acquisition Technologiesmentioning
confidence: 99%
“…The prevalent design for position tracking purposes employs a proportional or servo directional control valve and a constant-pressure hydraulic source to control the position of the hydraulic actuator, similar to what is shown at the right-hand side of Figure 1. A rich body of research is available on improving the position tracking performance, through using control design methods such as robust control, 7,8 nonlinear control, 9,10 adaptive control, 11 sliding mode control, 12 and combinations of these techniques. 13 These efforts have been successful judging by the experimental results they provide.…”
Section: Introductionmentioning
confidence: 99%